2017
DOI: 10.3389/fphys.2017.00950
|View full text |Cite
|
Sign up to set email alerts
|

The Clinicopathological and Prognostic Implications of FoxP3+ Regulatory T Cells in Patients with Colorectal Cancer: A Meta-Analysis

Abstract: Background and Objective: Forkhead box P3 (FoxP3) is known as the specific marker for regulatory T lymphocytes (Tregs), which are responsible for self-tolerance and disturb the antitumor immunity. However, the prognostic implication of tumor-infiltrating FoxP3+ Tregs in patients with colorectal cancer (CRC) still remains controversial. The aim of this present study was to investigate the prognostic role of FoxP3+ Tregs in CRC through meta-analysis.Methods: PubMed, Embase and Web of Science were searched for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 57 publications
(70 reference statements)
0
36
1
Order By: Relevance
“…Colorectal cancer (CRC) is one of the common malignant tumors of the digestive tract [1], which seriously threatens the life and quality of life of patients. In both sexes combined, the incidence of…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is one of the common malignant tumors of the digestive tract [1], which seriously threatens the life and quality of life of patients. In both sexes combined, the incidence of…”
Section: Introductionmentioning
confidence: 99%
“…Tumour-infiltrating lymphocytes (TILs) are a dominant immune component found in the stroma of primary tumour CRC samples. High densities of CD3 + , CD8 + , and Foxp3 + T cells were associated with prolonged survival and a significant therapeutic response in CRC patients [11][12][13][14]. Furthermore, TIL localization might also be associated with their function and clinical effect.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we have shown that activation of AhR by dietary indoles in a delayed-type hypersensitivity (DTH) model is essential for shifting the T cell response from a proinflammatory Th17 to an anti-inflammatory Treg phenotype [76]. This is important in regards to CRC as studies have shown that high expression of Tregs in CRC patients indicate a more favorable prognosis [77,78], whereas increased Th17 has been linked to CRC pathogenicity and tumor development [79][80][81]. The current report reinforces this notion, as gene expression data of CRC patients seemed to indicate that high expression of anti-inflammatory T cell factors (FoxP3, IL-10) improved patient survival, whereas proinflammatory makers linked to Th17 and Th1 phenotypes decreased overall survival in the patient population.…”
Section: Discussionmentioning
confidence: 99%